Public-Private partnerships in watershed management: evidence from the Himalayan foothills - Kurian, Mathew (2004)
Public-private partnerships have emerged in recent years as an important policy option to ensure service provision in the water resources sector. However, there is very little analysis of past experience of partnerships between the public sector and various arms of the private sector: water companies, NGO's or even farmers groups. Further, there is limited conceptualization of what is meant by partnerships between the public and private sectors. This paper draws on a study of watershed management in Haryana to analyze the evolution of public-private partnerships in natural resource management. The paper finds that the public sector has an important role to play in facilitating design of an institutional contract that clarifies water rights and rules for benefit sharing and conflict resolution. Interestingly, the paper finds that when a proper institutional structure is in place well endowed individuals with sufficient interest in a common pool good (like an irrigation system) may emerge to provide irrigation services with positive equity and efficiency outcomes for the environment and rural communities. However, the paper argues that State parastatals have an important role to play in monitoring impact of watershed management on traditionally marginalized groups like women and landless and coordinating inter-sectoral policy change to ensure that public-private partnerships can be sustained in the long term .